MEMBUMIKAN NILAI-NILAI TAUHID PADA SISWA SMP IT - Humaira, Husina; Amin, Mukayat Al (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
Islamic education in contemporary Indonesia faces the critical challenge of bridging theological principles with practical implementation in students' daily lives. The cultivation of tauhid values represents a paramount objective in Islamic educational institutions, particularly in integrated Islamic schools that seek to harmonize religious instruction with holistic character development. This study examines the implementation of tauhid values in the quotidian practices of students at SMP IT Zurriyatul Qurani Almaarif Lhokseumawe. As the fundamental tenet of Islamic faith, tauhid values necessitate internalization across all dimensions of students' existence, transcending mere cognitive comprehension to encompass practical embodiment in daily conduct. This study examines the implementation of tauhid values in the quotidian practices of students at SMP IT Zurriyatul Qurani Almaarif Lhokseumawe. As the fundamental tenet of Islamic faith, tauhid values necessitate internalization across all dimensions of students' existence, transcending mere cognitive comprehension to encompass practical embodiment in daily conduct. Employing a qualitative research paradigm, this investigation utilizes descriptive methodology. Data acquisition was conducted through systematic observation, in-depth interviews with pedagogical staff, students, and school administrators, complemented by documentation of instructional activities. The findings reveal that SMP IT Zurriyatul Qurani Almaarif Lhokseumawe implements a comprehensive pedagogical framework for actualizing tauhid values through curricular integration, systematic habituation of religious observances, exemplary modeling by educators, and establishment of an Islamic milieu. The manifestation of tauhid values is evidenced in students' moral disposition, theological comprehension, and devotional comportment. Identified impediments encompass exogenous environmental factors, technological advancement, and habituation consistency. This research advocates for robust collaborative synergy among educational institutions, familial units, and community stakeholders in fostering sustainable cultivation of tauhid values. ABSTRAK Pendidikan Islam di Indonesia kontemporer menghadapi tantangan kritis dalam menjembatani prinsip-prinsip teologis dengan implementasi praktis dalam kehidupan sehari-hari siswa. Menanamkan nilai-nilai monoteisme merupakan tujuan penting di lembaga pendidikan Islam, khususnya di sekolah-sekolah Islam terpadu yang berupaya menyelaraskan pengajaran agama dengan pengembangan karakter holistik. Penelitian ini mengkaji penerapan nilai-nilai tauhid dalam praktik sehari-hari siswa di SMP IT Zurriyatul Qurani Almaarif Lhokseumawe. Sebagai prinsip dasar agama Islam, nilai-nilai tauhid membutuhkan internalisasi di seluruh dimensi kehidupan siswa, melampaui  sekedar pemahaman kognitif semata hingga mencakup perwujudan praktis dalam perilaku sehari-hari. Penelitian ini bertujuan untuk menganalisis implementasi nilai-nilai tauhid dalam kehidupan sehari-hari siswa di SMP IT Zurriyatul Qurani Almaarif Lhokseumawe. Nilai tauhid sebagai fondasi keimanan Islam perlu diinternalisasikan dalam setiap aspek kehidupan siswa, tidak hanya sebagai pengetahuan kognitif tetapi juga sebagai praktik keseharian. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Data dikumpulkan melalui observasi, wawancara mendalam dengan guru, siswa, dan kepala sekolah, serta dokumentasi kegiatan pembelajaran. Hasil penelitian menunjukkan bahwa SMP IT Zurriyatul Qurani Almaarif Lhokseumawe menerapkan strategi holistik dalam membumikan nilai tauhid melalui integrasi kurikulum, pembiasaan kegiatan keagamaan, keteladanan guru, dan penciptaan lingkungan islami. Implementasi nilai tauhid tercermin dalam akhlak siswa, pemahaman keagamaan, serta perilaku ibadah sehari-hari. Tantangan yang dihadapi meliputi pengaruh lingkungan eksternal, perkembangan teknologi, dan konsistensi pembiasaan. Penelitian ini merekomendasikan perlunya sinergi yang kuat antara sekolah, keluarga, dan masyarakat dalam menanamkan nilai-nilai tauhid secara berkelanjutan.